Pseudomembranous Candidiasis Indicates High Level Drug Resistance among Patients on Antiretroviral Treatment in Nairobi East District, Kenya - Koyio LN; van der Sanden WJM; Jan Mulder; Dimba EO; Creugers NHJ; Merkx TMAW; Stelma FF; van der Ven Andre JAM (Journal of HIV for Clinical and Scientific Research - Peertechz Publications, 2015)
Objectives: The aim of this study was to determine antiretroviral drug resistance patterns in patients on long-term antiretroviral therapy presenting with OPC. Methods: An exploratory survey was performed among HIV-infected patients on ART for minimum of 24 months presenting with OPC in Nairobi, Kenya. Type (pseudomembraneous or erythematous candidiasis, angular cheilitis) and previous episodes of OPC, CD4-cell counts, duration, regimen and adherence on ART were compared between patients with high (>1000copies/ml) and low HIV-RNA levels. Genotypic resistance testing was performed on those with high viral loads. Results: Out of (n=45) patients with OPC, (n=28; 62%) had high HIV-RNA levels. The (n=28) patients who mostly presented with pseudomembraneuos candidiasis (n=26; p<.0001), had significantly more previous episodes of OPC (55% versus 18%; P<0.0373) lower median CD4 cell counts (74 versus 521; P<.0001) and higher HIV-RNA median plasma levels (111,191 copies/ml versus <20; P<.0001). The sensitivity (0.96) and specificity (0.87) of pseudomebraneous candidiasis to predict virological failure was high. HIV genotyping performed in 22 of the 28 patients showed that most (18/22) had drug resistance mutations of which 12/18 had Lamivudine-associated M184V mutation, 14/18 had TAMS and 16/18 had NNRTI mutations. One patient had major PI mutations. Conclusion: Virological failure and drug resistance mutations including TAMs should be suspected in patients on long-term ART that present with pseudomembraneous candidiasis. We propose to include recurrent OPC in the WHO clinical criteria for ART failure as well as to establish clinical training sessions to build competences among health care providers.